(untitled) (Journal of School Administration Research and Development, 2016)
As school leaders, 21st-century school administrators are in the spotlight for their role in promoting an environment of academic achievement. Along with organizing and planning for the fundamental workings of their staff, students, activities, and building, administrators are expected to encompass numerous roles. In fact, two primary, yet conflicting activities expected from school administrators are leading and managing (Hall & Simeral, 2008). At the intersection of these primary activities is the evaluation and development of teachers as a means to improve student learning. While the management of formal teacher evaluations and observations is important for ensuring teacher accountability and quality, administrators are also needed to use evaluation data along with student achievement data to improve teacher practice.